Exploration of Barriers in Achieving Proactive Environmental Strategies in a Natural Rubber Industry : A Case Study - Syarifa Arum Kusumastuti; Suprihatin Suprihatin; Nastiti Siswi Indrasti (Jurnal Riset Teknologi Pencegahan Pencemaran Industri, 2015)
As the evolving of environmental issues over time, the development of environmental management approaches in industries began to shift to the prevention of pollution to reduce environmental impact. However, in practice, many obstacles encountered during the environmental management change to be more proactive. This study aims to explore the barriers of achieving the proactive environmental strategy in a rubber processing industry. Used a case study approach in a natural rubber processing factory, the data was collected through interviews with experts and sources as well as observation in the field. This study shows main barriers that faced by the company consist of financial issue, human resources, communities’ pressure, technological change and communication with environmental experts. The results of this study suggest conducting cooperation with research institutions or environmental experts especially for skills that cannot be controlled by the manager or employees in the company.